Analisis Pengaruh Nilai Tukar Rupiah, Inflasi, dan Suku Bunga Bank Indonesia Terhadap Indeks Harga Saham Pertanian Yang Terdaftar di Bursa Efek Indonesia Periode 2013-2018 - Rani Puspitasari; Irianto Irianto; I Made Suardana (Fakultas Ekonomi Universitas Islam Al-Azhar, 2019)
The study aims to examine the effect of exchange rates of rupiah, inflations, and Bank Indonesia Interest rates to the movement of stock price index agriculture sector in Indonesia Stock Exchange. Sample were taken using saturation sampling. The data of this researches was secondary data period 2013 – 2018. Data were analyzed using Error Corection Model with Eviews aplication version 10. Therefore, In addition to assessing the goodness of fit a model tested t tes for testing partially, F test for testing simultaneously and coefficient of determination. The result of data analysis concluded in short term exchange rate of rupiah, Inflation, and Bank Indonesia Interest Rate had influeced and no significant. In long term the first Exchanges rate of rupiah had influeced negative and no significant. The second showed that inflation had influeced and no signifacnt. The third showed that Bank Indonesia Interest Rate had influeced postive and significant on the movement agriculture sector stock price index partially. The fourth result of this research showed Exchange Rate of Rupiah, Inflation, and Bank Indonesia Interest rate had influeced and significant on agriculture sector stock price index simultaneously. The results also indicate that the independence variables (exchange rates of rupiah, inflations, and Bank Indonesia interest rates) are able to explain the dependent variable (stock price index of agriculture sector) of 41,7% while the remaining 58,3%, the stock price indek of agriculture sector is affected by other variables outside regretion model.